The Implementation of Yusuf Al-Qaradawi’s Method of Understanding Hadith Regarding the Fatwa on the Meaning of Fi Sabilillah in the Context of Zakat - Yusronil Haq, Ahmad; Kholishudin (Al-Bukhari : Jurnal Ilmu Hadis, 2025)
This study aims to implement Yusuf al-Qaradawi’s method of understanding hadith in Kaifa Nata‘amal ma‘a al-Sunnah al-Nabawiyyah regarding the hadiths used as the basis for his fatwa on the the "Meaning of Fi Sabilillah in the Verse of Zakat." The background of this research is the importance of understanding the context of jihad in Islam in the modern era. The methodology employed is descriptive-analytical, involving steps such as explaining Yusuf al-Qaradawi’s method of understanding hadith and analyzing the implementation of this method in his fatwa. The results show that in his fatwa, Yusuf al-Qaradawi applies two methods of hadith understanding: compiling thematically related hadiths and distinguishing between the variable means and the constant objectives. The implication of this understanding method is that jihad in Islam is not limited to physical warfare but also encompasses efforts in da’wah and defending the faith. The means have shifted from tools of war to support for those engaged in da’wah. This study contributes significantly to contemporary understanding of jihad in Islam.